Menelisik Sikap Pemerintah Indonesia Dalam Menghadapi Kelangkaan Alat Pelindung Diri Ditengah Wabah Pandemi Coronavirus Disease (Ditinjau Dari Undang-Undang Nomor 36 Tahun 2009 Tentang Kesehatan) - Gondokesumo, Marisca; Amir, Nabbilah (UI Scholars Hub, 2022)
World Health Organization (WHO) has established coronavirus disease 2019 (COVID-19) as Public Health Emergency of International Concern (PHEIC), WHO recommends all countries to anticipate COVID-19. One important element needed to deal with the virus is personal protective equipment that is used by medical personnel to carry out medical treatment for patients infected with COVID-19, but the item is scarcity in Indonesia. What is the attitude of the Indonesian government in responding to the scarcity of personal protective equipment. The research method used is empirical juridical. The results showed that the scarcity of the availability of personal protective equipment due to the phenomenon of panic in the community who flocked to buy personal protective equipment. To overcome these conditions, the government established policies to facilitate the import of certain products, especially in the form of masks and personal protective equipment. As well as businesses temporarily prohibited from exporting personal protective equipment, if violated, sanctions will be given to him.